2023
DOI: 10.3390/nano13040716
|View full text |Cite
|
Sign up to set email alerts
|

Optical Gain of Vertically Coupled Cd0.6Zn0.4Te/ZnTe Quantum Dots

Abstract: The optical modal gain of Cd0.6Zn0.4Te/ZnTe double quantum dots was measured using a variable stripe length method, where large and small quantum dots are separated with a ZnTe layer. With a large (~18 nm) separation layer thickness of ZnTe, two gain spectra were observed, which correspond to the confined exciton levels of the large and small quantum dots, respectively. With a small (~6 nm) separation layer thickness of ZnTe, a merged single gain spectrum was observed. This can be attributed to a coupled state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In Ref. [31], Mei et al measured the VCQD optical modal gain of CdZnTe/ZnTe, where the lower QD is smaller; the results showed that the peak gain of the coupled QDs, separated 6 nm, was found comparable to the large separation QDs, 18 nm. Tongbram et al [32] researched on the multi-stacked vertically coupled InAs quantum dots capped by a combinational capping layer of InAlGaAs and GaAs layer.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [31], Mei et al measured the VCQD optical modal gain of CdZnTe/ZnTe, where the lower QD is smaller; the results showed that the peak gain of the coupled QDs, separated 6 nm, was found comparable to the large separation QDs, 18 nm. Tongbram et al [32] researched on the multi-stacked vertically coupled InAs quantum dots capped by a combinational capping layer of InAlGaAs and GaAs layer.…”
Section: Introductionmentioning
confidence: 99%